Integrated transcriptomic and metabolomic analyses reveal heterosis for meat quality of Neijiang pigs - Dan, Haifeng; Liu, Chengming; Zhang, Huiling; Gan, Mailin; Wang, Yan; Chen, Lei; Zhao, Ye; Liu, Bin; Zhu, Kangping; Niu, Lili; Zhu, Li; Shen, Linyuan (Frontiers in Veterinary Science, 2024)
Obese pig breeds have excellent meat quality, while lean pig breeds have high lean meat percentage and feed conversion rate. However, due to their respective shortcomings, obese pig and lean pig breeds are unable to balance production and consumption needs. Therefore, this study crossbred the obese Chinese pig breed Neijiang (NJ) with lean type Large White pigs (LW) to produce Neijiang × Large White(NL) pigs. This study compared the differences in carcass and meat quality traits between NJ pigs and NL pigs, and for the first time comprehensively analyzed the longissimus dorsi muscle of NJ pigs and NL pigs using transcriptomics and metabolomics. The results of slaughter and meat quality testing indicate that the carcass performance of NL pigs was significantly higher than that of NJ pigs, and the excellent meat quality characteristics of NJ pigs were also retained on NL pigs. The results of transcriptomics and metabolomics showed that there were 635 differentially expressed genes (DEGs) and 11 significantly different metabolites (SDM) in the longissimus dorsi muscle of NJ and NL pigs. The results of multi omics joint analysis showed that betaine, uridine triphosphate, glycerol 3-phosphate, and glutathione in SDMs were enriched in the shared KEGG pathway and significantly correlated with C1QTNF12, GGA3, SLC16A6, and RXRG in DEGs. In general, it is feasible to enhance the production performance of NJ pigs through crossbreeding with LW pigs. The hybrid offspring inherit the advantages of these two varieties, maintaining excellent meat quality while also having better carcass performance.